2018
DOI: 10.1002/stc.2212
|View full text |Cite
|
Sign up to set email alerts
|

Detection of slip for CFRP-concrete interface using stereovision method corrected by epipolar constraint

Abstract: The bond-slip relationship for the interface between concrete and carbon fiber reinforced polymer (CFRP) has become a hot research topic. Aimed at the disadvantage of traditional measurement approaches, a stereovision method corrected by epipolar constraint is proposed to measure slip curves of CFRPconcrete interface in the present paper. The proposed stereovision measurement method employs the epipolar constraint to correct digital image correlation (DIC) matching result. The nearest point located on the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although it is widely accepted, the application of strain gauges suffers from some limitations due to the a priori assumption of the uniform strain field, which practically recanted when cracking occurred [ 52 ]. In addition, strain gauges are locally limited, while PZT transducers can act in a wide spatial region.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is widely accepted, the application of strain gauges suffers from some limitations due to the a priori assumption of the uniform strain field, which practically recanted when cracking occurred [ 52 ]. In addition, strain gauges are locally limited, while PZT transducers can act in a wide spatial region.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the failure modes of CFRP-reinforced structures are often manifested as various types of debonding failure of CFRP-concrete interface (Zhang et al, 2017;Zeng et al, 2018;Rukavina et al, 2019). The ability to resist the deformation of FRP and concrete depends on the good bonding properties between CFRP and concrete (Yazdani et al, 2019;Wanga and Petrů, 2019;Shan et al, 2018;Li et al, 2018). Resaerch on the bond-slip relationship of CFRP-concrete interface is considered to be an in-depth study of CFRP strengthen methods applied to bridge (Yuan et al, 2019;Alhassan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%